Traumatic avulsion of the optic nerve - case report - Janicijevic, Katarina; Janicijevic Petrovic, Mirjana; Kocic, Sanja; Radovanovic, Snezana (PONS - medicinski časopis, 2016)
Optic nerve avulsion is a very rare but an extremely devastating complication of the eye injuries. The optic nerve is violently disinserted of the retina, choroid and vitreous, and lamina cribrosa drawn from the scleral rim. We reported the case of the older male person, who attempted suicide by firing a gun in the region of the abdomen and the right temple. After the provided clinical assistance which consisted of removing the spleen and disposal stab wound to the abdomen, under the general anesthesia, followed by the operation of the right eye injured, or enucleation of the eyeball with the reconstruction of conjunctival sac. Right eye was enucleated ovum of the forensic expertise (the hystopathological examination) which confirmed the complete acute section of the optic nerve. The patient was connected to the resuscitation apparatus because of the acute deep coma and after seven days he died. Keywords: attempted suicide, optic nerve, avulsion, enucleation, hystopathological examination